International Symposium on Archipelago Manuscripts VIII: In Search of Local Islam in Manuscripts - Yumi SUGAHARA (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
The production of Islamic manuscripts in the Archipelago increased from the 16th century through to the 18th century, particularly when Aceh became the centre of Islamic intellectual activities. A number of well-known 'ulama' came from this region, including Hamzah Fansuri, Shamsuddin al-Sumatrani, Nuruddin al-Raniri and Abdurrauf Singkel, who were extraordinarily productive in writing manuscripts, both for teaching and learning, and for other purposes. This manuscript writing tradition in Aceh then spread to a number of other areas in the Archipelago, such as Sulawesi, Java, and others. As a result, many Iocal manuscripts cat be found in these areas, which store knowledge specifically related to that area.DOI: 10.15408/sdi.v11i2.621